The Influence of Social Media and Product Quality on the Marketing Performance of Culinary Micro, Small, and Medium Enterprises (MSMEs) as Food Businesses in Pangururan - Febrianti Sinaga; Nalom Siagian; Natalia E. Sihombing (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to evaluate the influence of social media usage and product quality on the marketing performance of culinary Micro, Small, and Medium Enterprises (MSMEs) as food businesses in Pangururan. Using quantitative methods with multiple linear regression analysis on 60 sampled food businesses, the study found that both social media usage and product quality, both partially and simultaneously, have a significant positive impact on marketing performance. The regression model achieved an R2 value of 0.621, indicating these variables explain 62.1% of performance variance. Theoretically, these results highlight the critical synergy between digital interaction and physical product standards in resource constrained environments. Practically, the findings imply that culinary MSMEs must prioritize high quality visual content alongside strict hygiene and taste consistency to sustain competitiveness and drive repeat purchases in tourism hubs.